"It's a ripple effect": the role of intergroup contact within an inner-city youth sport for development and peace program. Issue 3 (3rd May 2020) - Brake, Jessica; Misener, Katie
ABSTRACT: Rationale: Positive contact between divided groups experiencing conflict may not only change intergroup attitudes, but may also promote positive relationship development and other community development outcomes. Purpose: The study draws on SDP literature and contact theory to investigate factors that facilitate positive intergroup contact within an inner-city youth SDP soccer program developed within the public sector. A secondary purpose is to examine the impact that contact has on program stakeholders including youth and authority figures within a community plagued with issues of youth deviance. Method: Semi-structured interviews were conducted with thirteen program stakeholders in one municipality in Ontario, Canada. Findings: Relevant programing, understanding others' perspectives, having champions of youth development, and human, financial, and partnership resources all play a critical role in facilitating contact within an inner-city youth SDP program. Intergroup contact also had many positive impacts on program stakeholders as trusting relationships were developed, youth behavior changed, and community pride was established. Practical Implications: Managers and policy makers can consider these factors when facilitating contact between diverse groups. Research Contribution: The study offers new insight into the role of public sector actors in SDP practice.